Analysis of Blood Eosinophil Levels as an Indicator of Controlled Asthma Classification at the University of Sumatra Utara Hospital - Damanik, Rizki Amaliah; Pradana, Andika; Pandia, Pandiaman (CoinReads Media Prima, 2025)
Introduction: Asthma is a chronic inflammatory disease of the airways characterized by variable airflow obstruction. Eosinophils play a crucial role in airway inflammation and may serve as a biomarker for asthma control classification. This study aims to analyze the relationship between blood eosinophil levels and asthma control classification in patients at the University of Sumatra Utara Hospital. Methods: This was an analytical observational study with a retrospective cohort approach based on medical records. A total of 25 stable asthma patients who had been receiving inhaled corticosteroid-long-acting beta-agonist (ICS-LABA) therapy for at least one year were included. Data were analyzed using SPSS version 26, and the Kruskal-Wallis test was performed to assess the relationship between eosinophil levels and asthma control classification. Results: The majority of patients were aged 26-50 years (44%) and female (80%). Most patients had eosinophil levels <100 (84%), while 8% had levels between 100-300 and another 8% had levels >300. Regarding asthma control, 46.7% of patients were fully controlled, 43.3% were partially controlled, and 10% were uncontrolled. Statistical analysis showed a significant relationship between eosinophil levels and asthma control classification (p = 0.009), indicating that lower eosinophil levels are associated with better asthma control. Conclusion: The study found that lower eosinophil levels were associated with better asthma control. These findings suggest that blood eosinophil levels may serve as an indicator for assessing asthma control, though further research is needed to confirm this relationship.